2016
DOI: 10.1186/s12940-016-0160-x
|View full text |Cite
|
Sign up to set email alerts
|

Public health and chronic low chlordecone exposure in Guadeloupe, Part 1: hazards, exposure-response functions, and exposures

Abstract: BackgroundInhabitants of Guadeloupe are chronically exposed to low dose of chlordecone via local food. The corresponding health impacts have not been quantified. Nevertheless the public authority implemented an exposure reduction program in 2003. We develop methods for quantifying the health impacts of chlordecone and present the results in 2 articles: 1. hazard identification, exposure-response functions (ERF) and exposure in Guadeloupe, 2. Health impacts and benefits of exposure reduction. Here is the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…Although this molecule is no longer used for two decades, significant concentrations persist in the soils and groundwaters of countries where CLD has been spread, making it one of the main pollutants found in table water and frequently found in rivers [ 95 , 96 ]. The latent presence of CLD represents a permanent danger for the exposed populations [ 95 , 96 , 97 ]. CLD exposure has been described to be associated with an increased incidence of various disorders, including breast cancer, prostate cancer, neurodegenerative and endocrine diseases, or fertility/fetal abnormalities [ 91 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ].…”
Section: Relation Between Pesticide Exposure and Cardiac Rhythm Disor...mentioning
confidence: 99%
“…Although this molecule is no longer used for two decades, significant concentrations persist in the soils and groundwaters of countries where CLD has been spread, making it one of the main pollutants found in table water and frequently found in rivers [ 95 , 96 ]. The latent presence of CLD represents a permanent danger for the exposed populations [ 95 , 96 , 97 ]. CLD exposure has been described to be associated with an increased incidence of various disorders, including breast cancer, prostate cancer, neurodegenerative and endocrine diseases, or fertility/fetal abnormalities [ 91 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ].…”
Section: Relation Between Pesticide Exposure and Cardiac Rhythm Disor...mentioning
confidence: 99%
“…Its persistence in the environment has resulted in a widespread contamination of Guadeloupean soils, water sources, animals and foodstuff leading to 95% of the population of Guadeloupe and 92% of that of Martinique being contaminated. Epidemiological studies showed that chronic low exposure to chlordecone is correlated with neurotoxicity and impaired neurobehavioral development (IQ point loss) in young children, characterized by a decrease in fine motor skills statistically significant only in boys [ 358 , 359 , 360 ]. However, there are no quantitative data for neurotoxic effects in adulthood in the French Antilles.…”
Section: Inhibition Of Gap-junctional Intercellular Communication mentioning
confidence: 99%
“…Several studies have suggested that exposure to endocrine disrupting compounds (EDCs) increases the risk of hormone-dependent cancers [ 3 , 4 ]. In fact, some of them are considered carcinogens by the International Agency for Research on Cancer (IARC), such as 2,3,7,8-tétrachlorodibenzo-p-dioxine (TCDD), some polychlorinated biphenyls (PCBs), dichlorodiphenyltrichloroethane (DTT) for PCa and BCa [ 5 , 6 ] or chlordecone for PCa [ 7 ]. Indeed, EDCs can mimic and/or interfere with hormone signaling and intracellular pathways implicated in numerous biological processes including cell proliferation, cell migration, invasion or apoptosis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%